Voluntary environmental regulation and export performance of Chinese solar energy industry - Sun, Ying; Lou, Jingyi; Sun, Huaping; Pan, Ting (Frontiers in Energy Research, 2023)
Motivated by the debate in the environment regulation and the trade liberalization literature, this article investigates the effect of voluntary environmental regulation on solar energy industry trade flows. The diffusion of ISO14001 standard is used to measure market-oriented voluntary environmental regulation. The results showed that export destination countries' voluntary environmental regulation has significant positive impact on export, while bilateral gap in voluntary environmental regulation has negative effect. A further investigation shows that reducing the bilateral gap in voluntary environmental regulation has a more obvious influence on the improvement of export to the developed countries than the developing countries. The moderating effect test confirms that the more trade friction will weaken the role of the host countries' diffusion of ISO14001 in promoting exports. We consider our findings not only within literature regarding the decision to pursue the ISO14001 certification responds to voluntary environmental regulation motivations, but also the subsequent policy implications of our findings in terms of solar energy industry bilateral trade.